2022
DOI: 10.1038/s41598-022-23190-0
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of circulating adaptive immune cells in patients with colorectal cancer

Abstract: Adaptive immune cells prevent solid tumor progression by targeting and killing tumor cells. However, there are no comprehensive studies on peripheral circulating adaptive immune cell characterization in colorectal cancer (CRC) patients or the effect of tumor-node-metastasis (TNM) stages on these cells. In this study, the number, phenotype, and function of different subsets of circulating adaptive immune cells in peripheral blood of CRC patients were analyzed. We found remarkable differences in CRC patients com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…CD3 + T cells in CRC patients were found to produce lower levels of IFN-γ, consistent with previous findings. 48 NKG2A, a co-inhibitory molecule, forms a heterodimer with CD94 on the surface of NK and T cells. 49 The non-classical MHC-I molecule HLA-E, a ligand of NKG2A, is widely found in numerous tumors, including colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…CD3 + T cells in CRC patients were found to produce lower levels of IFN-γ, consistent with previous findings. 48 NKG2A, a co-inhibitory molecule, forms a heterodimer with CD94 on the surface of NK and T cells. 49 The non-classical MHC-I molecule HLA-E, a ligand of NKG2A, is widely found in numerous tumors, including colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…An et al showed that CD4+/CD25+/FOXP3+ regulatory T-cells were significantly increased in patients with extensive stage small cell lung carcinoma when compared to controls, while an enhanced proliferation potential of CD8+ T-cells was indicative of better progression-free survival [28]. In addition, lower overall T-cell and cytotoxic/helper T-cell counts were noted in colorectal cancer patients vs. healthy controls [29].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early preoperative diagnosis can provide vital information for treatment-related decision-making. Immune cell subsets are currently an exciting target for CRC immunotherapy and early clinical diagnostic biomarker research because immune system regulation influences disease progression in patients with CRC 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%